Existence of Female Journalists Wearing Jilbab in the Television Media Jakarta - Rabathy, Qisthy; Komala, Elly; Susila Trisnawati, Yanti; Fadlah, Nik (Indonesian Journal of Social Science Research, 2021)
Female who wear jilbab is now choosing journalists as a job. Journalists are a job which exists in the middle of the community who is assigned to provide information or news to the public. This is a very heavy profession and not everyone can do this profession. Uncertain journalist working hours added with various difficulties and obstacles in this profession make this profession identified as a male profession. This becomes a challenge for journalists wearing jilbab who choose this job as their profession